Pengaruh Kualitas Layanan terhadap Kepuasan Pelanggan Transportasi Onlin - Gladies, Cyntia; Sabila, Laisyah; Prayoga, Moch.Restu; Ardianto, Robby Tri (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze the influence of service quality on customer satisfaction in online transportation service. The research is motivated by the growing competition in the digital transportation industry, which requires service providers to focus on customer satisfaction and loyalty through high-quality services and efficient technology. A quantitative approach was employed using a survey method involving 25 active users of online transportation service, with data collected through a Likert-scale questionnaire. Pearson correlation analysis revealed that service dimensions such as punctuality, driver attitude, and customer service have a very strong relationship with customer satisfaction. Multiple linear regression analysis confirmed that these factors significantly influence satisfaction, which in turn affects customer loyalty. On the other hand, features such as in-app functionality and travel time estimates were found to be statistically insignificant. The study concludes that service quality and effective use of technology are key factors in fostering satisfied and loyal customers in online transportation.